Reformative Approach of Sentencing in Nepal: Critical Study of Theory, Legal Framework and Praxis (Tribhuvan University Law Journal, 2025)
The article explores the idea of deterrence theory within the context of criminal justice systems. It focusses about how crime is a natural part of society and how rules and penalties are put in place to keep things in order. The article examines the history, philosophy, and rationale of deterrence theory, highlighting its goal of deterring crime by generating a fear of punishment in the public and potential offenders. It does this by drawing on qualitative and doctrinal research approaches. By examining philosophy, statutes and court rulings (case laws) in Nepal, it demonstrates how the deterrence theory affects sentence guidelines and the judgment of judges. Furthermore, the paper explores the human rights viewpoint on punishment and talks about how deterrence theory is used in Nepali law. To illustrate how courts understand and use deterrence theory in sentencing, case studies from Nepal and India are given. The article emphasizes on the judiciary’s responsibility in striking a balance between deterrence and other justice-related considerations. In a nutshell, the rationale of this paper is to provide insightful information about the philosophy and use of punishment in criminal justice systems with specific reference to Nepal.